Firms and industries in evolutionary economics: Lessons from Marshall, Young, Steindl and Penrose - Bloch, Harry; Finch, J. (Springer, 2010)
Evolutionary economists have tended to assess firms and industriesseparately, neglecting the role of their interaction in the process of economicgrowth and development. We trace the separation of firms and industries to theintroduction of population thinking in the discipline of industrial economics,including some broadly evolutionary analyses. If researchers conflate a populationof firms with an industry, they introduce “thin” means of relating firms toone another and to industries. Despite his device of the ‘representative firm’,Marshall develops “thick” means of relating firms to industries by means oftheir internal and external organizations. Penrose avoids the notion of industryby focussing on heterogeneous and potentially mobile firms. Young andSteindl develop mundane explanations of firms’ relations within groups andlocate the impetus for economic growth in a poorly understood environment.We conclude that evolutionary economists should revisit firms’ boundaries,not in the sense of explaining the existence of firms but in a relating andcommunicating sense in which boundaries signify the selective means of firms’relationships.